Respiratory status and behavioral response of premature infant with nesting model care approach in neonatal intensive care unit - Tuti Seniwati; Nurmaulid Nurmaulid; Abdul Kadir; Irmayanti Irmayanti (University of Muhammadiyah Malang, 2022)
Introduction: The increase in mortality of newborns, especially premature babies, is caused by non-optimal lung development where the production of less surfactant triggers lung collapse and compliance. This causes stress on the newborn and requires more intensive care. One of the care taken to overcome these problems is the nesting application. Objectives: To identify the effect of nesting model care on premature infants' respiratory status and behavioral responses. Methods: This study is a quasi-experimental design with a pre-post-test group design. The samples were premature infants admitted to the Neonatal Intensive Care Unit (NICU), with as many as 40 respondents. The sampling technique is purposive sampling. Data were analyzed using the Mann-Whitney test and Wilcoxon test. Results: The results showed no significant differences between the respiratory status in modern and conventional nesting, with P-value = 0.292. While there was a significant difference in behavioral responses, both groups with P = 0.027. There was an effect on respiratory status before and after nesting in the modern nesting group where the significance P = 0.001 and no effect in the conventional nesting group with a P value = 0066. Regarding behavioral responses, there was a significant value in two of the group before and after nesting, where the value significance respectively P = 0.009 and P = 0.025. Conclusions: Modern nesting influences scores and behavioral responses in premature infants, while conventional nesting only affects reducing the score of behavioral responses. It is expected that the use of nesting in the NICU room specifically for premature babies prefers the use of modern nesting compared to conventional nesting babies to maintain stability in terms of both respiratory and response behavior.